2013
DOI: 10.4028/www.scientific.net/amr.750-752.1347
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gelatin on Secondary Structure, Crystallinity and Swelling Behavior of Silk Fibroin - Gelatin Hydrogels and its Application in Controlled Release of Nitrogen

Abstract: Utilization of natural polymer as biodegradable matrix for the controlled releasing fertilizer can improve the performance of the materials and make them environmentally friendly. In this work, the effect of gelatin on the properties of hydrogels was investigated. The silk fibroin (SF)-gelatin hydrogels were prepared by solvent casting and β-crystallization of SF was promoted via methanol treatment. The secondary structure and the crystallinity of the blended hydrogels were investigated using Fourier transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…It can be hypothesized that PAA prevents the formation of PVA crystallites, leading to a material having higher amounts of amorphous zones. Materials having more amorphous zones usually exhibit larger swelling capabilities . This was observed in the blend materials here developed: PVA/PAA Mw 5000 hydrogels being less crystalline than PVA/PAA Mw 1800 showed greater swelling degree values than those achieved by the materials prepared from lower PAA's Mw.…”
Section: Resultsmentioning
confidence: 56%
“…It can be hypothesized that PAA prevents the formation of PVA crystallites, leading to a material having higher amounts of amorphous zones. Materials having more amorphous zones usually exhibit larger swelling capabilities . This was observed in the blend materials here developed: PVA/PAA Mw 5000 hydrogels being less crystalline than PVA/PAA Mw 1800 showed greater swelling degree values than those achieved by the materials prepared from lower PAA's Mw.…”
Section: Resultsmentioning
confidence: 56%
“…This indicates that the release mechanism of diffused urea molecules from the SF/gelatin/CS hydrogels is a super case II transport [20] which reflects the influence of matrix relaxation of the SF/ gelatin/CS on molecular movement of urea in the matrix. Comparing to our previous work [6], the release mechanism of diffused urea in the SF/gelatin hydrogel is quasiFickian from which the urea molecules diffuses partially through a swollen matrix and water filled pores in the hydrogels. But for the case of SF/gelatin/CS hydrogel, the water molecules penetrate the matrix followed by relaxation and swelling of the hydrogel network.…”
Section: Urea Release Behavior and The Release Kineticsmentioning
confidence: 78%
“…However, few researches has focused on their applications in agricultural area, especially in the field of controlled release fertilizer. In our previous work [6], the SF/gelatin hydrogels at various weight ratios were prepared and the urea release kinetics was investigated. The results revealed that the SF/ gelatin hydrogel, of which the SF/gelatin at a weight ratio of 75:25, released the urea at the slowest rate but only within a week.…”
Section: Introductionmentioning
confidence: 99%
“…Swelling ratios of the hydrogel substrates were obtained by measuring the weight before and after immersion in water at time intervals. The swelling ratio was calculated with eq . Three samples of each hydrogel type were tested. where W 0 and W t are the weights of hydrogels at initial time and time t , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…rGO was prepared from graphite using a modified Hammer’s method. , Briefly, 1 g of native graphite flakes was preoxidized by mixing with 1 g of P 2 O 5 , 1 g of K 2 S 2 O 8 , and 3 mL of H 2 SO 4 , and then incubated at 80 °C for 6 h. After washing with DI water and filtering, the preoxidized graphite was dried at 60 °C in an oven overnight. Subsequently, the preoxidized graphite powder was further oxidized in 23 mL of H 2 SO 4 with slow addition of KMnO 4 followed by stirring at 40 °C for 2 h. After 2 h, the reaction was terminated by adding 140 mL of distilled water.…”
Section: Methodsmentioning
confidence: 99%